Respon Pertumbuhan dan Produksi Kacang Tanah (Arachis hypogea L.) Terhadap Pemberian Pupuk Organik Asam Humat - Bahtiar, M Yusril Johan; Jumiatun, Jumiatun; Soelaksini, Liliek Dwi (Agropross : National Conference Proceedings of Agriculture, 2023)
Peanuts are a crop with a large demand in Indonesia after soybeans and will increase every year in the projected development of peanuts even until 2025. In Indonesia, especially in the East Java region as a center for Indonesian peanuts, production fluctuates due to inadequate land availability. . This study aims to assess the response of growth and production of peanut plants to doses of humic acid in Antirogo Village, Sumbersari District, Jember Regency. It was carried out from October 25 2022 to January 2023. This study was designed using a non-factorial randomized block design with a single factor, namely humic acid dose. The treatment consisted of 6 levels namely Control, 5kg/ha, 10kg/ha, 15kg/ha, 20kg/ha, 25kg/ha. These results were analyzed using ANOVA if they showed significantly different results then further tested using the BNJ level of 5%. The results showed that the application of humic acid at a dose of 25 kg/ha had a significant effect on the number of branches, fresh pod weight, and the SPAD value. The application of humic acid at a dose of 10 kg/ha had a significantly different effect on the parameter number of rich pods with an average of 36.38 rich pods.